Astrocyte-microglia interaction through C3/C3aR pathway modulates neuropathic pain in rats model of chronic constriction injury. (11th November 2022) - Mou, Wanying; Ma, Lulu; Zhu, Afang; Cui, Huan; Huang, Yuguang
Neuropathic pain (NP) is the cardinal symptom of neural injury, and its underlying molecular mechanism needs further investigation. Complements, especially complement 3 (C3), are involved in the pathophysiology of many neurological disorders, while the specific role of C3 in NP is still obscure. In this study, we found that both C3 and its receptor C3aR were upregulated in the spinal dorsal horn in a rat chronic constriction injury (CCI) model. In addition, C3 was mainly detected in astrocytes, while C3aR was expressed in microglia and neuron. Intrathecal injection of C3 antibody and C3aR antagonist alleviated NP in CCI model together with reduced M1 polarization of microglia. Our finding suggested that blockade of the C3/C3aR pathway might be a novel strategy for NP.